Reports from Channel 2 in 1992 and 1993
Discussion of the pervasive sexual violation of Bosnian women: estimated:20.000-60.000 victims. Red Cross sceptical about the figures. Confession of a Serb detention camp guard to rape under orders. Brief interview with alleged war criminal Damjanovic Sretko. Refugees. Life in a detention camp. A military prison in Sarajevo. Footage of Vukovar. Wounded in the streets and hospitals.